2023
DOI: 10.1108/ijqrm-11-2022-0316
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the performance of quality management practices induced by top management commitment and Kaizen initiatives: evidence from Jordanian public hospitals in the aftermath of COVID-19

Abstract: PurposeThis study investigates the effects of top management commitment (TMC) and Kaizen on quality management practices (QMP) and how the latter influence the performance of Jordanian public hospitals in the aftermath of COVID-19.Design/methodology/approachA survey-based questionnaire was employed to collect data from 222 practitioners and professionals working in public hospitals in Jordan. Partial least squares structural equation modeling (PLS-SEM) was undertaken to analyze data.FindingsSignificant and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Total quality management (TQM) and SC partnership are two important concepts that have been widely studied in the field of operations management (Kaur, 2019). Both concepts are different and have been shown to have a significant impact on the SP of organizations (Alsmairat et al , 2023; Zaid and Sleimi, 2023). TQM is a management approach that aims to continuously improve the quality of products and services to meet or exceed customer expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Total quality management (TQM) and SC partnership are two important concepts that have been widely studied in the field of operations management (Kaur, 2019). Both concepts are different and have been shown to have a significant impact on the SP of organizations (Alsmairat et al , 2023; Zaid and Sleimi, 2023). TQM is a management approach that aims to continuously improve the quality of products and services to meet or exceed customer expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Kaizen principles, which are founded on the notion of implementing small gradual changes, have won widespread acclaim for their revolutionary influence on business operations, employee engagement and organizational performance (Helmold et al ., 2022; Kumar et al ., 2023c). Previous year research studies (Hundal et al ., 2022; Demirtas et al ., 2022; Alsmairat et al ., 2023) demonstrated that a dedication to continuous improvement results in higher effectiveness, decreased waste and increased competitiveness. Participation of employees at all levels in the process of improvement is prioritized by Kaizen concepts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Amidst this disrupted environment, the long-standing principle of “Kaizen” emerged as a helping hand for businesses striving to navigate the unpredictable challenges of the COVID-19 pandemic era (Demirtas et al ., 2022). The recognized Kaizen operations, which emphasize gradual and continual improvement, have shown to be important resources for businesses not just during the COVID-19 epidemic, but also to negotiate the unclear post-pandemic environment (Alsmairat et al ., 2023). The concept of Kaizen principles has given businesses a way to navigate the enormous obstacles offered by the COVID-19 pandemic and its consequences, enabling them to not only survive but even grow (Demirtas et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%